The Impact of the One-Stop Integrated Service of the Department of Education and Youth on the Acceleration of Educational Administration - Darmaji, Fransiscos Xavirius; Wijaya, Petra Surya Mega (Jurnal Ar Ro'is Mandalika (Armada), 2025)
This study explores the impact of the One-Stop Integrated Service (OSS) of the Department of Education and Youth on the acceleration of educational administration. The implementation of OSS aims to streamline administrative processes, improving efficiency and responsiveness within the education sector. Using a mixed-methods approach, the research evaluates how OSS has influenced the speed and quality of educational service delivery. Data was collected through surveys and interviews with key stakeholders including administrative staff, educators, and policy makers. The findings reveal that OSS has significantly reduced the time required for processing educational documents, thereby enhancing service accessibility and transparency. Moreover, the study highlights challenges such as resource limitations and the need for continuous staff training to maintain the effectiveness of the OSS model. The results suggest that the OSS framework plays a crucial role in accelerating educational administration, contributing to the overall improvement of the education system. This research provides valuable insights into the implementation of integrated service systems in educational governance, offering recommendations for further optimization and scalability.